Sonship in the Bible - Joshua Maurer; Amy Peeler (St Andrews Encyclopaedia of Theology, 2022)
The people of Israel and the early Christians considered themselves to be in a privileged familial relationship with God. It is this special status as ‘sons’ which necessitates careful examination of this theme throughout the biblical narrative. First, it is vital to apprehend, as much as is possible, the cultural dynamics of sonship among the people groups from whom these texts arose. Then, close attention to the specific stories of sons in Israel’s scriptures and the New Testament will allow the reader to see elements of consistency as well as distinctiveness between types of sonship. In the First or ‘Old’ Testament, the unexpected experiences of individual sons demonstrate Israel’s sense of gracious election by God. In the Second or ‘New’ Testament, the central figure of Jesus is known prominently as both Son of God and Son of Man. Tracing these identities throughout the canonical text allows a foundation upon which to understand the communities who confessed Jesus’ sonship as those who were then described as adoptees into the family of God. This article seeks to introduce students to resources and biblical texts vital for engaging with the theme of sonship. This common word takes on many complicated meanings and implications; readers of the biblical text must inquire which are at play in any particular instance of the theme. Special attention is given to the entailments of sonship (its gender exclusivity noted and discussed) for the people of Israel and the early believers in Jesus.